2019
DOI: 10.1186/s13256-019-2280-8
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary abscess: two case reports

Abstract: BackgroundPituitary abscess is a rare condition with nonspecific symptoms that can be delayed. Proper diagnosis needs to occur preoperatively so that the management can be set up accordingly. Accurate diagnosis is challenging because many differential diagnoses can exhibit the same magnetic resonance imaging features.Case presentationWe report two cases of pituitary abscess. The first patient was a 66-year-old Arab woman who underwent a surgical procedure for a pituitary macroadenoma and presented 3 months lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Pituitary hormone deficiencies persist in the majority of patients following treatment Up to 70% of patients with PA can have central Diabetes insipidus. In contrast, fever with signs of meningeal irritation is reported in 25% of cases [5]. MRI is the imaging of choice for the pituitary lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pituitary hormone deficiencies persist in the majority of patients following treatment Up to 70% of patients with PA can have central Diabetes insipidus. In contrast, fever with signs of meningeal irritation is reported in 25% of cases [5]. MRI is the imaging of choice for the pituitary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of PA is nonspecific, such as headaches, pituitary hypofunction, and visual disturbances, whereas the infection can be discreet and inconstant [5,6]. Symptoms can be acute, subacute, or chronic, explaining the late diagnosis; in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-related hypophysitis represents 30% of all primary forms [12], is characterized by a mononuclear infiltration enriched in lymphocytes and plasma cells, with more than 10 IgG4-positive cells per HPF and typical morphological features (storiform fibrosis or obliterative phlebitis) [7,8,13]. Non-infectious pituitary abscess or sterile abscess are a controverse entity, indeed in some Authors' opinion, sterile abscess results from liquefaction of necrosis of an infarcted pituitary gland or the contents of an atypical pituitary cyst [14,15]. However-as in the current case-patients typically present with no fever, no leukocytosis, and culture results are negative.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pituitary abscess is slightly more common in females. Most of the published literature focusing on pituitary abscess were case reports [1,3], with the most significant number of cases (66 cases) in [8]. It has been shown that preoperative diagnosis of a pituitary abscess is challenging [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…More than 300 patients have been reported so far were misdiagnosed before surgery [2]. Before surgery, a preliminary diagnosis is essential for formulating surgical plans and perioperative management [3]. Imaging is the primary method to confirm the diagnosis of pituitary abscess before surgery.…”
Section: Introductionmentioning
confidence: 99%